Assessing the Contribution of Local and Traded Biodiversity in Community Health Care: A case study from Keelakodankulam village, South India - Mary, D.; Franco, F; Babu, V. (University of Hawaii Press, 2011)
The study aims to assess the contribution of local and traded biodiversity towards community health care. A total of 106 knowledge holders from the Aatha Pallar community were interviewed and medicinal uses for 70 local plants and 28 plant products purchased from the market were recorded. The Pharmacological Ethnobotanical index was found to be low suggesting knowledge erosion. About 13 plant species used by the community show high Use Value Indices. A majority of the plants used in the community’s medicinal system come from the immediate locality and only a minor part comes from the market, though ones from the market tend to have high use value indexes. The study illustrates that local medicinal plant diversity is important for community health care, which in turn, ensures conservation of the local medicinal plant diversity.